Efficacy and tolerability of high- versus low-dose lenalidomide maintenance therapy of multiple myeloma after autologous blood stem cell transplantation - Fenk, Roland; Giagounidis, Aristoteles; Goldschmidt, Hartmut; Heinsch, Michael; Rummel, Mathias; Kroger, Nicolaus; Boquoi, Amelie; Lopez, David; Gerrlich, Celina; Baier, Julia; Liesenjohann, Svenja; Hauck, Katarzyna; et al. (Clinical cancer research, 2020)
Purpose: For multiple myeloma, high-dose chemotherapy and autologous blood stem-cell transplantation (ASCT) followed by lenalidomide maintenance (LenMT) at 10-15 mg/day is considered standard of care. However, dose reductions due to side effects are common and median LenMT doses achieved over time may remain lower. Dose response during LenMT has never been investigated. - Patients and Methods: In a multicenter, randomized, open-label trial, patients with multiple myeloma after ASCT and high-dose lenalidomide consolidation therapy (CT) at 25 mg/day were randomized to receive LenMT at either 25 or 5 mg/day. Primary endpoint was progression-free survival (PFS). - Results: Ninety-four patients (median age, 58 years) were randomized to either arm, with 22% having International Staging System (ISS) stage 3 and 22% being in complete remission (CR). After median follow-up of 46.7 months, median doses of 14.5 and 5 mg/day were achieved in the two arms; 53% of dose reductions occurring during CT. In the high- and the low-dose arm, median PFS was 44.8 and 33.0 months (HR, 0.65; 95% CI, 0.44-0.97; P = 0.032), 36% and 23% of patients had stringent CR as best response (P = 0.08), and 4-year OS was 79% and 67% (P = 0.16), respectively. Hematologic toxicity, grade ≥3 neutropenia, and infections were initially more common with LenMT 25 mg, but decreased after dose adjustments. SPM incidence and quality-of-life (QoL) scores in both arms were similar. - Conclusions: LenMT dose correlated with efficacy and toxicity. High rates of dose reductions during CT argue against a high starting dose. However, continuous up- and down-titration for each patient to the current maximum tolerated dose is prudent.
Gesehen am 26.01.2021